Balances de nitrógeno y fósforo a escala predial, en sistemas lecheros pastoriles en Argentina - Herrero, M.A. (2006)
Nutrient balance allows to know the potential environmental risk in productive systems. Nitrogen (N) and Phosphorus (P) balances and their utilization efficiencies were evaluated, at farm level, through three indicators in primary milk production systems in Buenos Aires. The balance calculation was made by measurable output-input differences for each mineral in 17 farms, expressed as ton/year and in terms of production (N-P (grams)/ milk production (liters)). Both balance magnitudes, in ton/year showed association with the size of the farm, but not when they were expressed as product. The principal N inputs were external foods and nitrogen fixation and for P were the fertilizers. Nutrient inputs resulted to be between 4 and 7 times larger than the outputs through milk and meat produced by the dairy farm. The indicatorsrevealed larger nutrient inefficiencies in grazing systems than in more intensively managed systems cited in international bibliography. Phosphorus appears to be the nutrient used less efficiently. The evaluation of the balances turns out to be a necessary tool to diminish nutrients losses looking for the best productive, profitable and environmental equation, through the whole understanding of the system itself.